Acupuncture and Depth: Future Direction for Acupuncture Research. (8th July 2014) - Goh, You Li; Ho, Chin Ee; Zhao, Baixiao
Abstract : The research on acupuncture has increased steadily over the years and regular review and revision of the direction of future acupuncture research are necessary. This paper aims to review and explore the significance of acupuncture depth in modern acupuncture research. Searches conducted in Science Direct and China National Knowledge Infrastructure (CNKI) databases reflected a lack of focus on depth of acupuncture. We propose that the research trends of acupuncture should progress to the depth of insertion. It is suggested that future acupuncture research, especially randomized controlled trials (RCTs), should take into consideration the depth of insertion. Comparison between databases using different language of medium suggests the need for international collaboration of researchers from the same field. It is also crucial to inherit and innovate traditional medicine (TM) through modern technology. The use of bibliometric method is also suitable for development of TM research trends. Acupuncture and depth should be considered as one of the future directions of acupuncture research.